Relationships and revised status of Nagathrips (Thysanoptera: Phlaeothripinae) - Varatharajan, R.; Johnson, Th.; Tarunkumar, Singh (Zootaxa, 2017)
The generic name Nagathrips was erected as a sub-genus of Mesothrips for the single species, crenulatus Varatharajan and Singh (2000). Subsequent studies revealed character states that were not included in the original description. These are: prosternal basantra absent; antennal segment III with one slender sense cone, segment IV with three similar sense cones; fore wings parallel-sided with no median constriction. These character states are not found in any species of Mesothrips, a genus of the Tribe Haplothripini (Mound & Minaei 2007), but are typical of members of the Liothrips-lineage (Dang et al. 2014). To confirm such a relationship partial sequence data of the mitochondrial gene (CO1) was obtained and compared with that of Gynaikothrips species.